Analisis ANALISIS JARINGAN KOMUNIKASI PETANI KELAPA SAWIT SWADAYA DI DESA SURYA INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - M. Akhyar Rosadi (Jurnal Agribisnis, 2020)
ABSTRACT This study aims to (1) examine the patterns of communication networks, (2) actors involved in communication networks, (3) and their role in oil palm farmers in Surya Indah Village, Pangkalan Kuras District, Pelalawan Regency. The sampling method used in this study was to use a non probability sampling technique consisting of purposive sampling and snowball sampling technique. The results showed that based on the communication network formed in the four agribusiness subsystems, it could be seen that it was still dominant in the wheel pattern, the network structure in the form of a wheel pattern was a very centralized pattern. The roles found in the communication network formed are star, bridge and gate keeper. Analysis of individual level communication networks to see actors who are stars, suitable actors as information disseminators and actors as communication control holders. The star actors in the upstream subsystem are Subariadi (SB): self-help extension workers, Subar Mantono (SM): oil palm farmers, Kasman (KS): oil palm farmers, and Agricultural Shops (TP): input production traders. In the farming subsystems are Subariadi (SB), Subar Mantono (SM), and PT Surya Bratasena (PTSB), the downstream subsystems are Rokhim (RO), Siswanto (SO), and Miskam MS: palm oil tauke, the supporting subsystem is BRI (BR), Miskam (MS), and Rokhim (RO). Actors suitable as information disseminators in the upstream subsystem are Subariadi (SB), in the farming subsystem namely Subariadi (SB), in the downstream subsystem namely Nanda (NA): Head of Surya Indah Village, Subariadi (SB), Subar Mantono (SM), and in the supporting business subsystem, namely Sukardi (SK): oil palm farmers. The actor who acts as communication control in the upstream subsystem is Subariadi (SB), the farming subsystem is PT Surya Bratasena (PTSB), the downstream subsystem is Rokhim (RO), and the supporting business subsystem is Rokhim (RO). Keywords: star, bridge, gatekeeper.